Impact of collaborative learning on student engagement in college English programs: mediating effect of peer support and moderating role of group size - Hong Li (Frontiers in Psychology)
Collaborative learning (CL) and student engagement have been extensively researched. There are few studies on the interaction between college students and its underlying mechanism. This research investigates how CL activities assist in boosting student engagement in English programs at public sector colleges. A purposive sampling of 425 intermediate students from a Chinese public college was used to evaluate the direct impact of CL on engagement, the mediating effects of peer support and the moderating influence of group class using structural equation modeling (SEM). The findings show that CL positively relates to peer support but not students’ engagement, and the relationship between peer support and engagement is also significantly positive. However, the specific indirect impact indicates that specific peer support mediates CL activities and students’ engagement to a whole extent. Our results underscore CL’s potential to improve students’ engagement. The results indicated that peer support increases students’ engagement when the group size is less than others. This study is significant for instructors, administrators, educators, policymakers, students, and researchers seeking effective techniques to enhance student engagement in English programs and learning.